Determining a Statistical Analysis for the Quantitative Study in Research - Mweshi, Geoffrey Kapasa; Muhyila, Mildred (Advances in Social Sciences Research Journal, 2024)
The manner in which research will be conducted follows from the research questions or hypotheses; the type of research must be in support of the project. Several types of research are conducted in studies, including experimental, quasi-experimental, and observational research. Researchers must weigh the advantages and drawbacks of each type of research to determine which design is best for their specific research questions or hypotheses. Alternately, researchers can employ several methods, known as triangulation, to provide a varied and complementary perspective. The use of several methods, measures, or theoretical frameworks to examine a particular phenomenon or behavior improves the robustness of study and can corroborate findings across the various measures (Keyton 2014). Quantitative Designs states the research questions the study will answer, identifies the variables, and states the hypotheses (predictive statements) using the format appropriate for the specific design. For a quantitative study, the theory(ies) or models(s) guides the research question(s) and justifies what is being measured (variables) and describes how those variables are related. Quantitative study: Describes each research variable in the study discussing the prior empirical research that has been done on the variable(s) and the relationship between variables. The overall structure for a quantitative design is based on the scientific method. It uses deductive reasoning, where the researcher forms a hypothesis (Albers, 2017), collects data in an investigation of the problem, and then uses the data from the investigation, after analysis is made and conclusions are shared, to prove the hypotheses not false or false